Seed morphology and anatomy of Hypericum majus (A. Gray) Britton - Szkudlarz, Piotr; Celka, Zbigniew; Rosadziński, Stanisław; Wojciechowicz, Maria Katarzyna (Biodiversity: Research and Conservation, 2019)
Investigations were conducted based on samples originating from three localities in Central Europe (Poland). The obtained results showed that H. majus seeds are very small – about 0.5 mm in length. In the SEM image, their surface is reticulate, typical of majority of species in this genus. Anatomical analysis showed that seed coat of matured seeds is very delicate, composed of two cell layers with strongly lignified walls.